Regional Administration and Local Government Local Government Reform Programme Implementation Report 1998-2088 - Prime Minister's Office (Dar es Salaam Prime Minister's Office, 2008)
The Government of Tanzania has been implementing its policy of Decentralisation by Devolution(D-by-D) through the Local Government Reform Proramme(LGRP) to improve local governance and service delivery.This report provides a detailed analysis of the Local Government Reform Programme from 1998 to 2008, identifying important lessons for designing and implementing decentralisation reforms.
Keywords: Local Government